Inhibition of ADAM10 promotes the clearance of Aβ across the BBB by reducing LRP1 ectodomain shedding. Issue 1 (December 2016) - Shackleton, B.; Crawford, F.; Bachmeier, C.
Abstract Background Transport across the blood–brain barrier (BBB) is an important mediator of beta-amyloid (Aβ) accumulation in the brain and a contributing factor in the pathogenesis of Alzheimer's disease (AD). One of the receptors responsible for the transport of Aβ in the BBB is the low density lipoprotein receptor-related protein 1 (LRP1). LRP1 is susceptible to proteolytic shedding at the cell surface, which prevents endocytic transport of ligands. Previously, we reported a strong inverse correlation between LRP1 shedding in the brain and Aβ transit across the BBB. Several proteases contribute to the ectodomain shedding of LRP1 including the α-secretase, a desintegrin and metalloproteinase domain containing protein 10 (ADAM10). Methods The role of ADAM10 in the shedding of LRP1 and Aβ BBB clearance was assessed through pharmacological inhibition of ADAM10 in an in vitro model of the BBB and through the use of ADAM10 endothelial specific knock-out mice. In addition, an acute treatment paradigm with an ADAM10 inhibitor was also tested in an AD mouse model to assess the effect of ADAM10 inhibition on LRP1 shedding and Aβbrain accumulation. Results In the current studies, inhibition of ADAM10 reduced LRP1 shedding in brain endothelial cultures and increased Aβ42 transit across an in vitro model of the BBB. Similarly, transgenic ADAM10 endothelial knockout mice displayed lower LRP1 shedding in the brain and significantly enhanced Aβ clearance across the BBB compared to wild-type animals. Acute treatment with the ADAM10-selective inhibitor GI254023X in an AD mouse model substantially reduced brain LRP1 shedding and increased Aβ40 levels in the plasma, indicating enhanced Aβ transit from the brain to the periphery. Furthermore, both soluble and insoluble Aβ40 and Aβ42 brain levels were decreased following GI254023X treatment, but these effects lacked statistical significance. Conclusions These studies demonstrate a role for ADAM10 in the ectodomain shedding of LRP1 in the brain and the clearance of Aβ across the BBB, which may provide a novel strategy for attenuating Aβ accumulation in the AD brain.